Didactic discourse and its impact on the learning process in higher education. (UNIHumanitas, 2013)
This paper presents the thesis proposal to achieve the degree of Interuniversity Master in Quality Teacher Training for Pre-university and University Teaching in Language and Literature Didactics, whose purpose is oriented to the diagnosis and analysis of the type of didactic discourse and its impact on the learning process in higher education. On the basis that the classroom is an educational space with particular forms of communication, in which learning is a social activity that involves interaction between participants and the resources they use, exchange of information, and a priority use of language as a medium and as an action, we specifically propose the investigation of aspects such as the type of didactic discourse that prevails during the development of classes, the pedagogical model on which the didactic discourse used by teachers in the classroom is based, the discursive genres most used by teachers in the didactic discourse during the development of their classes, the impact of the didactic discourse used by teachers on students' learning, and the attitude shown by students towards the types of didactic discourse used by teachers during the development of classes.
Keywords: didactic speech; discursive genres; language; interaction